Library Staff members' picnic. - Unknown:::Creator::::::::::::
Written on verso: "Mr. Gordon Martin; Mrs. Gordon Martin; Mabel Carlson; J. Van; Rachel Nyswander; Dora Smith; Gloria Wickham; Dorothy Lawton; Marion Pack; College Library picnic at Caroline Bailey's Aug 1952; Library Staff Members."